Reaction of cocoa clones and hybrids to Ceratocystis fimbriata and inheritance of resistance - Gardella, D.S. (1980)
Tesis (Mag. Sc.) -- CATIE, Turrialba (Costa Rica) -- Universidad de Costa Rica, San José (Costa Rica), 1980